Revisão sobre técnicas de controle em estruturas inteligentes - Da Silva, Samuel [UNESP]; Júnior, Vicente Lopes [UNESP] (My University, 2005)
One of the great challenges of structural dynamics is to ally structures lighther and stronger. The great difficulty is that light systems, in general, have a low inherent damping. Besides, they contain resonance frequencies in the low frequency range. So, any external disturbance can excite the system in some resonance and the resulting effect can be drastic. The methodologies of active damping, with control algorithms and piezoelectric sensors and actuators coupled in a base structure, are attractive in current days, in order to overcome the contradictory features of these requeriments. In this sense, this article contributes with a bibliographical review of the literature on the importance of active noise and vibration control in engineering applications, models of smart structures, techniques of optimal placement of piezoelectric sensors and actuators and methodologies of structural active control. Finally, it is discussed the future perspectives in this area.
A review of control techniques in smart structures
Keywords: Optimal placement of sensors/actuators; Optimization; Smart structures; Vibration control; Natural language processing systems; Piezoelectric actuators; Resonance; Structural dynamics; Light systems; Optimal placement of sensors; Structural active control; Intelligent structures